2005
DOI: 10.1111/j.1365-2567.2005.02168.x
|View full text |Cite
|
Sign up to set email alerts
|

The phenotype of type 1 and type 2 CD8+ T cells activated in vitro is affected by culture conditions and correlates with effector activity

Abstract: Summary We used various culture conditions to generate type 1 (Tc1) or type 2 (Tc2) cytotoxic T cells in vitro. T‐cell receptor (TCR) transgenic T cells were cultured with antigen and spleen cells, or antigen and dendritic cells (DC), or anti‐CD3 and anti‐CD28. Tc1 cultures contained interleukin (IL)‐2 and IL‐6, and Tc2 cultures contained IL‐2, IL‐6 and IL‐4. Tc2 cells generated in each culture condition acquired a CD62Llow CD44high phenotype, had high cytotoxic activity, and secreted IL‐4, IL‐5 and moderate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 35 publications
2
26
3
Order By: Relevance
“…1C). This pattern of expression is similar to that reported previously for type 1 and type 2 polarized CD8 T cells generated in vitro by activation with peptide-coated splenocytes in cytokine-polarizing conditions (18). Following overnight restimulation of purified Va2 + cells with anti-receptor Ab, upregulation of expression of mRNAs encoding the type 2 cytokines IL-4, IL-5, IL-10, and IL-13 was evident in both groups exposed to IL-4-expressing tumors; however, expression of mRNA for type 2 cytokines and the type 2 transcription factor GATA-3 was more prominent in the absence of IFN-g ( Fig.…”
Section: Cr Release Assaysupporting
confidence: 73%
“…1C). This pattern of expression is similar to that reported previously for type 1 and type 2 polarized CD8 T cells generated in vitro by activation with peptide-coated splenocytes in cytokine-polarizing conditions (18). Following overnight restimulation of purified Va2 + cells with anti-receptor Ab, upregulation of expression of mRNAs encoding the type 2 cytokines IL-4, IL-5, IL-10, and IL-13 was evident in both groups exposed to IL-4-expressing tumors; however, expression of mRNA for type 2 cytokines and the type 2 transcription factor GATA-3 was more prominent in the absence of IFN-g ( Fig.…”
Section: Cr Release Assaysupporting
confidence: 73%
“…A number of earlier studies have shown that IL-4 induces both the de novo production of IL-4 and down-regulation of CD8 expression in activated CD8 ϩ T cells (12)(13)(14)22). Important clinical correlates have been reported in HIV infection and chronic B cell lymphocytic leukemia, in which IL-4-expressing CD8 ϩ T cells with reduced CD8 expression have been described and may be associated with disease progression (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies found that CD62L lo sorted, ex vivo activated effectors, transferred without concomitant vaccination or cytokines, were more effective at inducing tumor rejection than unsorted cells [7,8], and that infiltration of CD62L lo T cells correlated with an objective response against the tumors [7,20,21]. Similarly, we have previously reported that anti-tumor activity correlated with the presence of CD62L lo cells in the adoptively transferred CD8 1 T-cell populations [6]. Several factors may explain these contrasting observations.…”
Section: Discussionmentioning
confidence: 73%
“…Our culture conditions also used IL-2, but this was only for a short period of time, and only after T cells had already undergone full activation in the presence of Ag. Co-culture with BM-DC, instead of the frequently used spleen APC [5,[7][8][9]19] Line318 T cells activated in vitro in the presence of spleen APC have weak anti-tumor activity in vivo [6], suggesting that the type of APC is important in determining the activity of the resulting T cells. Further experiments are in progress to determine the culture conditions that are critical to the generation of our powerful anti-tumor T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation